Re-engineering payment systems for the E-world - Harry Leinonen (Bank of Finland, 2000)
Payment systems are undergoing rapid changes stimulated largely by technological progress.Distributed network technology, real-time processing and customers' willingness to use electronic banking interfaces will further reshape payment systems during the coming years.Internet and e-commerce will have a major impact on payment systems. This paper presents the current developmental trends.It analyses the need to develop payment standards and the content of payment instructions in order to fully automate the payment process.Since interbank settlements comprise an essential part of payments, they should be made an integral part of the payment process within the Internet environment.With cross-border payments increasing in importance, any new developments should take an international perspective. Payment system development requires cooperation between the banks and other participants involved.In order to build the necessary consensus, banking industry organizations as well as central banks and other regulators will need to work together to re-engineer the present payment systems, making full use of the possibilities created by modem technology.
URN:NBN:fi:bof-20140807558
Keywords: 330; payment systems; settlement systems; RTGS; payment system integration